2015
DOI: 10.1080/02678292.2015.1011717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hofmeister anions on the existence of the biaxial nematic phase in lyotropic mixtures of dodecyltrimethylammonium bromide/sodium salt/1-dodecanol/water

Abstract: Lyotropic mixtures including different sodium salts of Hofmeister anions were studied in order to investigate the effect of these anions on the existence of biaxial nematic phase and on the uniaxial to biaxial phase transitions. For this purpose, these sodium salts were added singly into different mixtures of dodecyltrimethylammonium bromide (DDTMABr)/1-dodecanol/water, keeping the relative molar concentration of all the constituents constant. The uniaxial to biaxial phase transitions were determined from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…For this reason, complementary investigations were needed to understand the effect of the specific interactions between the ionic species at the micelle surfaces on the stabilization of the lyotropic nematic phases, especially the biaxial. Sodium salts of some Hofmeister ions were added [12] to the host lyotropic mixture of dodecyltrimethylammonium bromide (DTMABr)/dodecanol (DDeOH)/water. The results showed that the interactions between the positively charged head group of DTMABr, trimethylammonium, and the Hofmeister series kosmotropic (SO4 2− , F − , Cl − ), and chaotropic (Br − , NO3 − , I − , ClO4 − ) anions play an important role on stabilizing the lyotropic nematic phases.…”
Section: Effect Of Interactions Between Head Groups and Ions Of Electmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, complementary investigations were needed to understand the effect of the specific interactions between the ionic species at the micelle surfaces on the stabilization of the lyotropic nematic phases, especially the biaxial. Sodium salts of some Hofmeister ions were added [12] to the host lyotropic mixture of dodecyltrimethylammonium bromide (DTMABr)/dodecanol (DDeOH)/water. The results showed that the interactions between the positively charged head group of DTMABr, trimethylammonium, and the Hofmeister series kosmotropic (SO4 2− , F − , Cl − ), and chaotropic (Br − , NO3 − , I − , ClO4 − ) anions play an important role on stabilizing the lyotropic nematic phases.…”
Section: Effect Of Interactions Between Head Groups and Ions Of Electmentioning
confidence: 99%
“…Although the results of [12] provided useful results about the stabilization the different nematic phases, it was necessary to generalize the role of specific interactions on the micelle's surfaces in terms of the kosmotropic and chaotropic properties of both the surfactant head groups and the counterions/ions. For this purpose, three surfactant molecules were selected, two of them with chaotropic head groups (one positively charged, the other negatively charged) and one with a negatively charged kosmotropic head group.…”
Section: Effect Of Interactions Between Head Groups and Ions Of Electmentioning
confidence: 99%
See 2 more Smart Citations
“…Three different LNPs are defined in the literature. They are discotic nematic (ND), calamitic nematic (NC) and biaxial nematic (NB) phases [6][7][8][9]. From the optics point of view, the first two ones are uniaxial and the latter one is biaxial.…”
Section: Introductionmentioning
confidence: 99%